TIME LOSS AND INJURY CHANGES WITH MULTIDISCIPLINARY PREVENTIVE APPROACH IN FEMALE VOLLEYBALL PLAYERS. Issue 7 (11th March 2014) - Mendes de Almeida Gomide Leite, M; Bolling, C; Reis, D; Bittencourt, N; Gonçalves, G
Abstract : Background: Youth volleyball players have high injury rates in shoulder, knee and ankle. Specific preventive programs could reduce time loss and injury severity reflecting in athlete's performance. Objective: To describe the difference in time loss and injuries occurrence after a multidisciplinary prevention approach in youth volleyball athletes. Design: This is longitudinal and prospective study. Setting: The data colection and interventions were conducted with volleyball players competing in a national level in a Brazilian sports club. Participants: 42 female youth volleyball athletes with a mean age of 13.8 years (±1.4), body mass of 59.2 (±8.6) kg and height of 171.2 (±5.5 cm ). Intervention: A multidisciplinary preventive approach (MPA) was characterized by CORE, knee and ankle stabilization exercises during warm up. Shoulder rotators, gluteus maximus and hamstrings muscles were trained in strengthening sessions. Main outcome measurements: The MPA was conducted by team's physiotherapist and coach, performed twice a week, with 20 minutes duration. Injuries and time loss was reported by the team's physiotherapist. Results: There was a 60% reduction of days out of training and 10% reduction in the number of injuries. Conclusions: MPA reduces the time loss and injuries occurrence in youth volleyball athletes. It is important to design preventive interventions by the injury profile, focusing in most predisposed injured areas. Time loss and lower injury occurrence reflect in athletes' performance.